Proteomic analysis of crevicular fluid of traumatized primary teeth - Jorge, Paula Karine (2018)
Traumatic dental injuries (TDI) often happens in early childhood, the examination method is clinical and radiographic. Another methodology that has been used to aid in TDI diagnosis is molecular biology. A fluid that has been studied in molecular biology is gingival crevicular fluid (GCF), which is an appropriate fluid to evaluate the relation between periodontal tissues and pulp, and its compounds will depend on either the health or inflammation level of tissues. Therefore, this study aimed to characterize the proteins/peptides in GCF of primary tooth with different sequelae of TDI to clarify the proteins/peptides functions in order to contribute in the diagnosis of pulp and periodontal conditions. The sample was composed for 8 children with TDI, ranging 4 to 6 years. GCF samples were collected in 4 points of the gingival sulcus of both the 12 traumatized teeth and the 8 primary first molar, divided into 5 groups: Molar group (deciduous first molar), No alteration, Pulp Canal Obliteration (PCO), Repair-Related Resorption (RRR) and Pulp Necrosis (PN). GCF proteins were subjected to liquid chromatography electrospray ionization mass spectrometry for identification and characterization. 436 single proteins/peptides were found in this study. 43 (9.86%) were in No alteration group, 92 (21.10%) in PCO group, 23 (5.28%) in RRR group, 16 (3.67%) in PN group, and finaly, 114 (26.15%) in molar group. All groups revealed the following peptides/proteins functions: immune response, cell degradation and recycling, repair and maintenance, enzymatic process, cell binding, cell signaling, cell differentiation, cell migration, structural components and antioxidant activity. Proteins functions related to the specific groups: molar group played role in homeostasis process. No alteration group, I6L9F6_HUMAN, NEB2_HUMAN, Q5T0H8_HUMAN, H0YJG4_HUMAN are related to nervous tissue, and, TET1_HUMAN to odontoblast differentiation. RRR group, CALX_HUMAN, B8ZZF0_HUMAN are related to senescence, and KMT2D_HUMAN mutation is associated to skeletal deformation. PCO group, CATA_HUMAN is response to hypoxia, fibroblast transformation, and osteoblast differentiation; MTA70_HUMAN is related to stem cell differentiation; ITPR2_HUMAN releases calcium ion into cytosol. Fistula group: Q8TAS6_HUMAN development of neuronal tissue; E9PDR3_HUMAN neurotransmitter release, cell division and death; B4DT36_HUMAN play a role in conducting axon; C9JN07_HUMAN mitotic process; RSF1_HUMAN DNA repair; Q19KS2_HUMAN immune defense. Concluding, TDI of primary tooth profile undergoing different sequelae type was characterized. The proteins of molar group exhibited complete homeostasis. In no alteration group, the proteins play a role in maintaining the nervous tissue. The proteins of PCO group were involved in cell transformation and differentiation to reach canal root obliteration. The proteins of RRR group revealed a senescence process. In fistula group the proteins play a role to surround the inflammation site.